Incidence and risk factors of postoperative sore throat after endotracheal intubation in Korean patients. (April 2017) - Lee, Jin Young; Sim, Woo Seog; Kim, Eun Sung; Lee, Sangmin M; Kim, Duk Kyung; Na, Yu Ri; Park, Dahye; Park, Hue Jung
Objective: To investigate the incidence of postoperative sore throat (POST) in Korean patients undergoing general anaesthesia with endotracheal intubation and to assess potential risk factors. Methods: This prospective study enrolled patients who underwent all types of elective surgical procedures with endotracheal intubation and general anaesthesia. The patients were categorized into group S (those with a POST) or group N (those without a POST). The demographic, clinical and anaesthetic characteristics of each group were compared. Results: This study enrolled 207 patients and the overall incidence of POST was 57.5% ( n = 119). Univariate analysis revealed that significantly more patients in group S had a cough at emergence and hoarseness in the postanaesthetic care unit compared with group N. Receiver operating characteristic curve analysis showed that an intracuff pressure ≥17 cmH2 O was associated with POST. Multivariate analysis identified an intracuff pressure ≥17 cmH2 O and cough at emergence as risk factors for POST. At emergence, as the intracuff pressure over ≥17 cmH2 O increased, the incidence of hoarseness increased. Conclusions: An intracuff pressure ≥17 cmH2 O and a cough at emergence were risk factors for POST in Korean patients. Intracuff monitoring during anaesthesia and a smooth emergence are needed to prevent POST.